(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
Our article is devoted to the analysis of the social sphere of society and the role of the state in the formation and implementation of social policy. We consider key aspects of social policy, including social protection, health care, education, labor relations, housing construction and pension provision. The emphasis is on the relationship between social processes and the economic situation, as well as on how state institutions influence the improvement of the quality of life of citizens. The article also analyzes current problems of social policy, including its effectiveness in the context of modern challenges and changes in society.